ACTR-37. ASSOCIATION BETWEEN MGMT PROMOTER METHYLATION SCORE AND SURVIVAL IN PATIENTS WITH GLIOBLASTOMA. (11th November 2019) - Romo, Carlos; Shah, Pavan; Sun, Yuqing; Ye, Xiaobu; Grossman, Stuart
Abstract: BACKGROUND: MGMT promoter methylation is associated with longer survival in patients with high-grade gliomas who receive alkylating therapy. Methylation status is commonly determined by methylation-specific PCR and results are reported in two forms: a dichotomization of "present" or "not present, " and as a methylation score (MGMT/beta-actinx1000). The primary objective of this study is to determine the association between the degree of methylation and overall survival (OS) in newly diagnosed patients with glioblastoma. METHODS: A retrospective IRB-approved study was conducted of 684 patients treated at Johns Hopkins from 2007–2015. Adults with a histologically confirmed glioblastoma treated with standard therapy were included in the analysis. OS was estimated from the date of diagnosis to time of death or last follow up using the Kaplan–Meier method. Cox regression model was used to assess possible positive association between MGMT score and OS. For purposes of this analysis IDH1-mutated patients were excluded. RESULTS: In 100 evaluable patients, median age at diagnosis was 56 years [45–77]. Fifty-two patients were MGMT promoter methylated (score ≥2.00) and 48 were unmethylated. The median OS was 31 months in the methylated patients and 15 months in the unmethylated (p=0.0001). Methylated patients had MGMT scores ranging from 2.53-1278. The methylated scores were classified into 3 groups; #1: 0-25th percentile, #2: 25-75th percentiles, and #3: >75th percentile. mOS was: 30.8 months for group 1 (n=13); 34.8 months for group 2 (n=27); and 20.9 months for group 3 (n=12) (p=0.19). Difference in mOS between groups 1 and 3 was not statistically significant (HR 0.819 [95% CI, 0.3–2.2], p=0.69). DISCUSSION: The prognostic value of MGMT promoter methylation in patients with glioblastoma was replicated in our study sample. The degree of methylation reported as a score on routine testing does not appear to be directly related to OS in this patient population.